The Development of Canadian Conspectus On-Line/ La developpement du Service Recherche Conspectus Canadian - Otto, Paul; Crandlemire, Debbie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF